Determinants of Trade Flows and Trade Structure between Korea and ASEAN - Hoan Quang Truong; Chung Van Dong; Hoang Huy Nguyen (East Asian Economic Review (EAER), 2019)
Our paper contributes to existing literature by empirically investigate the trade structure and trade performance between Korea and ASEAN. Overall, trade activities between Korea and almost major ASEAN economies have significantly focused on capital goods, medium and high technology goods, while the remaining ASEAN countries' exports over Korea have been mainly primary and low technology goods. There has been a higher complementarity in between Korea's exports and ASEAN's imports compared with between ASEAN's exports and Korea's imports. Estimation results show that ASEAN's GDP and income have larger impacts than those of Korea on aggregate trade flows as well as sectoral level between two sides. Additionally, geographical conditions are critical factors impeding Korea-ASEAN trade. Meanwhile, other factors in the estimation model have mixed impacts on components of Korea-ASEAN trade structure. Finally, there is a significant room for Korea's trade expansion with ASEAN, particularly new and less developed members in future.
Keywords: B27; F10; F13; F14; 330; ASEAN; Gravity Model; Korea; Trade Performance; Trade Structure